2016
DOI: 10.1016/j.taap.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Mustard vesicant-induced lung injury: Advances in therapy

Abstract: Most mortality and morbidity following exposure to vesicants such as sulfur mustard is due to pulmonary toxicity. Acute injury is characterized by epithelial detachment and necrosis in the pharynx, trachea and bronchioles, while long-term consequences include fibrosis and in some instances, cancer. Current therapies to treat mustard poisoning are primarily palliative and do not target underlying pathophysiologic mechanisms. New knowledge about vesicant-induced pulmonary disease pathogenesis has led to the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 159 publications
(220 reference statements)
3
38
0
Order By: Relevance
“…By comparison, VPA had no effect on NM-induced alveolar epithelial barrier dysfunction, as measured by BAL protein levels, or on structural alterations in the respiratory tract. These findings suggest that there are multiple mechanisms underlying the pathologic and cytotoxic effects of NM in the lung (Weinberger et al, 2016). Previous studies demonstrated that VPA was effective in reducing acute lung injury induced by LPS, ischemia-perfusion and sepsis (Ji et al, 2013;Kim et al, 2012;Shang, et al, 2010;Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…By comparison, VPA had no effect on NM-induced alveolar epithelial barrier dysfunction, as measured by BAL protein levels, or on structural alterations in the respiratory tract. These findings suggest that there are multiple mechanisms underlying the pathologic and cytotoxic effects of NM in the lung (Weinberger et al, 2016). Previous studies demonstrated that VPA was effective in reducing acute lung injury induced by LPS, ischemia-perfusion and sepsis (Ji et al, 2013;Kim et al, 2012;Shang, et al, 2010;Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Oxidative stress has been shown to contribute to vesicant-induced lung injury, in part by triggering the inflammatory cascade. 3,41,42 Thus, following exposure to vesicants, antioxidant levels decrease, and markers of oxidative stress, such as malondialdehyde, 8-hydroxyguanosine, and 4-hydroxynonenal, increase. [43][44][45] Additionally, treatment of animals with antioxidants reduces vesicant-induced lung injury and inflammation.…”
Section: Mustard-induced Oxidative Stressmentioning
confidence: 99%
“…Hence, findings of this study may elucidate ineffectiveness of the current practice in management of the COPD and IPF which did not take in to account this undeylying immunopathological mechanism. Currently, there is no the Food and Drug Administration (FDA) approved protocol for treatment of the SM induced pulomonary complications 16 and this novel finding may help to establish a desired treatment protocol.…”
Section: Relationship Between Expression Of the Cytokines And Clinicamentioning
confidence: 99%
“…For they, a curative treatment is not available up to now. 15,16 In addition, some studies have demonstrated that the levels of local and systemic proinflammatory cytokine may be different, which causes different regulation mechanisms in the local and circulating cytokines. 17 Hence, we evaluated mRNA expression of proinflammatory cytokines, IL-1β, TNFα and TNFR1, at the local position in the lung formalin-fixed, paraffinembedded (FFPE) section of SM-exposed subjects and non-exposed patients.…”
Section: Introductionmentioning
confidence: 99%